Professional Identity Formation in the Transition From Undergraduate to Postgraduate Medical Education: A Scoping Review - Juliana Sá; Ana L. Da Silva; Pia Strand; Simon Kitto (The Clinical Teacher, 2026)
ABSTRACT Background The transition from undergraduate to postgraduate medical education is a crucial phase of professional development, requiring trainees to assume greater clinical responsibility and adapt to new social norms. This transition influences professional identity formation (PIF), which is important for safe practice, well‐being and resilience. We conducted a scoping review to map studies of PIF during this transition and synthesise the key findings of this body of literature. Methods We searched five databases for studies published between January 2000 and December 2023. Eligibility criteria guided inclusion. We extracted relevant information and PRISMA‐ScR reporting elements and used inductive thematic analysis to synthesise findings. Results Twenty‐one studies met the inclusion criteria, representing mixed‐methods, qualitative and quantitative designs and diverse theoretical approaches to PIF. Only one study explicitly defined ‘transition’. Most studies ( n = 14) were descriptive; two were justification studies, and five aimed to clarify mechanisms, contextual influences and theoretical underpinnings. Four themes described factors influencing PIF in the transition from undergraduate to postgraduate education: navigating the self, the system, clinical practice and collaboration. Conclusions Supporting early‐career doctors requires more than fostering resilience. Training environments must reduce systemic barriers, model professional values and create relational spaces where emerging doctors can belong, reflect and grow. Future research should move beyond description towards theoretically informed, multi‐context studies that examine mechanisms underlying these influences and generate transferable, actionable knowledge for those supporting trainees during this transition.